Foreign countries' experience of coordination based on tax control - PhD Ismailov Bobir Salomovich (Genius Journals, 2025)
This article presents the conclusions and conclusions that can be drawn from the analysis of the possibilities of tax authorities to identify possible cases of tax evasion, ensure fair taxation, and ultimately contribute to the overall efficiency of the tax system by improving the practice of auditing and monitoring taxpayers' activities. The article highlights the advantages and problems of applying foreign experience in the conditions of Uzbekistan, and develops proposals and recommendations for improving national tax policy.
Keywords: tax revenues; risk analysis; risks